Production potential of rainfed pearl millet (Pennisetum glaucum)-castor (Ricinus communis) intercropping at different fertility levels - Kumar, Ashok; Gautam, R C; Kaushik, S K (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during the rainy season of 1990 and 1991 to study the production potential of rain fed pearl millet [Pennisetum glaucum (L.) R Br. emend. Stuntz] + castor(Ricmus communis L.) intercropping at different levels of fertility. Data on castor-seed yield revealed that pearl millet for grain + castor gave better environment for castor to grow than pearl millet for fodder + castor Sole castor, however, proved best for the individual yield, whereas intercropping of pearl millet for fodder + castor was the best for pearl millet-grain-yield equivalent, followed by pearl millet for grain + castor. Sole crop of . castor was not found remunerative. Soil-fertility levels improved the plant height, dry-matter accumulation, yield attributes and yield of pearl millet and castor linearly. Application of farmyard manure@ 10 tonnes/ha was found superior to the control only. Application of 2 bio-fertilizers. ie Azostrithum and vesicular arbuscular mycorrhiza. also showed favourable response in dry-matter accumulation and yield. In terms of pearl millet-grain- equivalent yield and gross return. 40 kg N/ha + 8.80 kg P/ha proved statistically superior to 20 kg N/ha + 4.4 kg P/ha.